"All I See Is Your Booty and Cleavage": Sex and the Contemporary Gospel Song (1988–2017). Issue 4 (November 2021) - Pollard, Deborah Smith
Abstract: Gospel songs traditionally feature lyrics that glorify God. However, there is music by contemporary gospel artists that addresses pre-marital sex, homosexuality, and pornography. The fact that these topics are being lyrically confronted by some of the genre's most recognized performers invites exploration into the content, purpose, and impact of the songs. This article places these lyrics into categories: those that are testimonial narratives about the spiritual deliverance the singer has received after transgressing sexual mores of the Black Church and those that encourage the avoidance of specific sexual practices. These songs contribute to gospel music on several levels, providing a platform through which the artists can testify of their sexual journeys while giving listeners a format through which they can find direction regarding sexual steps, missteps, and spiritual realignment. The article delineates the changes within US culture that led to less silence about sex and support for the LGBTQIA+ community from some within the Black Church. The major analysis involves the lyrics, the differences in what men and women tend to address, and the fact that despite breaking new ground, in virtually every instance, they reflect traditional Biblical interpretations.